2001
DOI: 10.1111/hdi.2001.5.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension Is Associated with Increased Serum Lipoprotein(a) Levels in End‐Stage Renal Disease Patients

Abstract: In addition to disorders in lipoprotein metabolism, several other factors are involved in the development of atherosclerotic changes in end-stage renal disease (ESRD) patients. One of these is arterial hypertension. We evaluated serum lipids-total cholesterol (TC), triglycerides (TG), apolipoproteins (A , A , B, E), lipoprotein(a) [Lp(a)]-in 109 ESRD patients on dialysis [46 on hemodialysis (HD); 63 on continuous ambulatory peritoneal dialysis (CAPD)] and in 45 hyperlipidemic patients without renal failure (HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…Fytili et al showed significantly higher Lp(a) values in hemodialysis patients with hypertension than in those without hypertension. They emphasized that hypertension may play an important role in serum Lp(a) titers in end-stage renal disease patients on dialysis [31]. Finally, as we found no significant difference in Lp(a) concentration between those with or without statins, a potential confounding effect by statin use [32] and its impact on Lp(a) concentration did not seem likely to explain the lack of association between Lp(a) and cardiovascular diseases in French Guiana.…”
Section: Discussioncontrasting
confidence: 48%
“…Fytili et al showed significantly higher Lp(a) values in hemodialysis patients with hypertension than in those without hypertension. They emphasized that hypertension may play an important role in serum Lp(a) titers in end-stage renal disease patients on dialysis [31]. Finally, as we found no significant difference in Lp(a) concentration between those with or without statins, a potential confounding effect by statin use [32] and its impact on Lp(a) concentration did not seem likely to explain the lack of association between Lp(a) and cardiovascular diseases in French Guiana.…”
Section: Discussioncontrasting
confidence: 48%
“…21,22 The pathogenicity and atherogenic role of Lp (a) is highly influenced by the concentration of other serum lipids and lipoproteins. 23,24,25 Several investigators reported correlation between Lp (a) and other lipid variables. In the present study, a significant correlation was observed between HDL and LDL cholesterol levels and Lp (a).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Indian population have shown that Lp (a) levels are significantly higher among pulmonary arterial hypertension 27 (mean 31.6 mg/dL). Recent report from Fytili et al 23 suggested that arterial hypertension is associated with elevated Lp (a) levels in patients with end-stage renal disease. In their study, it was observed that Lp (a) levels were significantly higher in the hypertensive patients, but that difference was not significant among non-renal failure patients.…”
Section: Resultsmentioning
confidence: 99%